Modelling and control of crystallization process; Resource-Efficient Technologies; Vol. 3, iss. 1 : TECHNOSCAPE 2016: International Conference on Separation Technologies in Chemical, Biochemical, Petroleum and Environmental Engineering - Jha S. K. (2017, 2017)
Title screen